Penalty kick or not? Differences in the interpretation of handball incidents in professional association football - Tobias Bauch; Daniel Leyhr; David Schmidt; Daniel Brinkmann; Oliver Höner (PLoS ONE, 2026)
Handball decisions in the penalty area remain one of the most controversial topics in professional association football, yet they are underexplored in sports science. The purpose of this research was to establish a foundation for understanding the controversy by examining its underlying causes. Two video-based studies quantified how key stakeholders interpret handball incidents and how closely these interpretations align with Union of European Football Associations (UEFA) guidelines. Study 1 involved referees active in German men’s professional football ( n = 154) who judged 30 incidents. Study 2 repeated the procedure with professional coaches ( n = 31) and players ( n = 46) using 18 incidents. Outcomes were Accuracy (accordance with UEFA), Strictness (percentage of incidents deemed punishable), Consensus (within- and between-group agreement), and Reasoning (primary reason for a decision). Referees reached 84.0% Accuracy, which differed by role, performance level, and handball category. Strictness among referees was lower compared to UEFA (42.9% vs. 50%). Coaches and players demonstrated lower Accuracy (63.8% and 67.5%) and Strictness (36.0% and 33.9%) than referees, resulting in significant differences in Consensus across Stakeholder Groups in 11 out of 18 incidents. Reasoning also diverged as referees preferred Naturalness, whereas coaches and players emphasised Avoidability and Impact. These findings reveal systematic differences between governing body guidelines, referee decision-making, and practitioner expectations. The results can inform educational measures and discussions on potential revisions to the handball law. Clearer and more objective criteria, jointly agreed by key stakeholders, are required to improve the consistency and acceptance of handball decisions.